Comparison of Hemoglobin Concentration Before and After Trichuriasis Treatment with Albendazole among Primary School Children - Sipayung, Novreka P; Arrasyid, Nurfida; Pasaribu, Ayodhia P (Indonesian Journal of Medicine, 2016)
Background: Trichuriasis is a soil transmitted helminth that causes anemia and growth disturbance in children. This study aimed to compare hemoglobin concentration before and after Trichuriasis treatment with albendazole among primary school children.Subjects and Method: This was an experimental study with before and after quasi experiment design. This study was conducted at Medan Tembung Primary School, Medan, North Sumatera, from March to June, 2015. A total of 63 children were selected for this study. Blood sample was taken for hemoglobin concentration examination before and after the administration of albendazole. The treatment consisted of 400 mg albendazole that was administered in single dose 0nce a day for 3 days, both for single and mixed infection.Results: The prevalence of Trichuriasis among the school children under study was 33.3% (126/ 378), which was consisted of 37 children with single infection and 26 children with mixed infection. Albendazole increased hemoglobin concentration with mean= 11.88 g/dl; SD=1.26 before treatment and mean=12.53 g/dl; SD= 1.37 after treatment, among children with single infection, and it was statistically significant (p= 0.002). Albendazole increased hemoglobin concentration with mean= 11.69 g/dl; SD=1.04 before treatment and mean=12.36 g/dl; SD= 1.06 after treatment, among children with mixed infection, and it was statistically significant (p= 0.001).Conclusion: Albendazole is effective in increasing hemoglobin concentration among school children with anemia that is caused by Trichuriasis infection.ÃÂ Keywords: helminthiasis, trichuriasis, hemoglobin, anemia, albendazole, school childrenCorrespondence: Novreka Pratiwi Sipayung. Department Parasitology, Faculty of Medicine, HKBP Nommensen University, Medan. Email: ega_efq@yahoo.com.ÃÂ Mobile: 085261145049.Indonesian Journal of Medicine (2016), 1(4): 201-208https://doi.org/10.26911/theijmed.2017.02.01.08